Modeling of a ground wire using TLM - Wan Ahmad, Wan Fatinhamamah; Thomas, D. W. P.; Christopoulos, C. (2008)
This work is aimed at developing electromagnetic modeling techniques to enable researchers to predict the behaviors of substation grounding system to lightning strikes using a 1-D transmission-line model. Several simulations have been done using 1-D TLM algorithm with two different injection impulses for comparison purpose. The method has been validated by contrasting with an algorithm based on a distributed model of an electrode where a good agreement was found. And, it is important for the selection of allowable one segment length of the 1-D transmission-line model to be less than 20% of its total length to produce reliable and accurate results of the transient responses.